2021
DOI: 10.3390/ma14154344
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of Curcumin–DNA Interaction by Using Hydroxyapatite Nanoparticles–Ionic Liquids Based Composite Electrodes

Abstract: Hydroxyapatite nanoparticles (HaP) and ionic liquid (IL) modified pencil graphite electrodes (PGEs) are newly developed in this assay. Electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and cyclic voltammetry (CV) were applied to examine the microscopic and electrochemical characterization of HaP and IL-modified biosensors. The interaction of curcumin with nucleic acids and polymerase chain reaction (PCR) samples was investigated by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The changes in CU and guanine oxidation signals were monitored via DPV (Figure 6). The same procedure was applied using also PCR samples and the results were in good agreement with those obtained by gel electrophoresis [109]. It was shown that, in the presence of Cu 2+ ions, CU damaged the DNA molecule due to the formation of a Cu 2+ -CU complex that interacted with DNA and the generation of reactive hydroxyl radicals.…”
Section: Cu Interaction With Dnasupporting
confidence: 69%
“…The changes in CU and guanine oxidation signals were monitored via DPV (Figure 6). The same procedure was applied using also PCR samples and the results were in good agreement with those obtained by gel electrophoresis [109]. It was shown that, in the presence of Cu 2+ ions, CU damaged the DNA molecule due to the formation of a Cu 2+ -CU complex that interacted with DNA and the generation of reactive hydroxyl radicals.…”
Section: Cu Interaction With Dnasupporting
confidence: 69%
“…40 ILs could be used in the structure of sensors and biosensors for the detection of several types of drugs in water and real samples. [41][42][43][44] N-Buty-3-methylimidazolium tetrafluoroborate (N-B-3-MITFB) IL was used for the synthesis and application of a magnetic carbon quantum dots electrochemical sensor used for the detection of raloxifene and tamoxifen. It was a supersensitive sensor with a 10.0 nM limit of detection that showed properties like good reproducibility and suitable repeatability in comparison to other works.…”
Section: F I G U R E 1 Scheme Of Different Methods Used For the Fabri...mentioning
confidence: 99%
“…ILs could be used in the structure of sensors and biosensors for the detection of several types of drugs in water and real samples 41–44 . N ‐Buty‐3‐methylimidazolium tetrafluoroborate ( N ‐B‐3‐MITFB) IL was used for the synthesis and application of a magnetic carbon quantum dots electrochemical sensor used for the detection of raloxifene and tamoxifen.…”
Section: Application Of Ils In Electrochemical Sensorsmentioning
confidence: 99%
“…The DNA-curcumin interaction was followed also at a hydroxyapatite (HaP) NPs and ionic liquid (IL)-based pencil graphite electrode (PGE) [42]. In a different report, the enhanced electrochemical response from the f-CNT-modified GCE was used to evaluate the chemical and biochemical behavior of curcumin in the presence of transition metal ions copper (II) and dsDNA [30].…”
Section: Electrochemistry Of Curcuminmentioning
confidence: 99%